Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jad.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Mood-worsening with high-pollen-counts and seasonality: A preliminary report

Abstract: Background: Because aeroallergens produce inflammation in the respiratory airways, and inflammation triggers depression in vulnerable individuals, we hypothesized that mood sensitivity to pollen, the most seasonal aeroallergen, will be associated with a greater seasonality of mood. Since pollen is absent during winter, we specifically predicted that mood sensitivity to tree pollen will predict non-winter SAD but not winter SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
(42 reference statements)
3
23
0
Order By: Relevance
“…In a self-report study, self-reported lower moods were associated with high pollen counts, with seasonality different than seasonal affective disorder (i.e., fall-winter mood worsening) [120]. Subjective worsening of mood with high pollen counts, which is similar to season of pollen exposure, has been reported previously in college students [121].…”
Section: Ar and Depressionmentioning
confidence: 75%
“…In a self-report study, self-reported lower moods were associated with high pollen counts, with seasonality different than seasonal affective disorder (i.e., fall-winter mood worsening) [120]. Subjective worsening of mood with high pollen counts, which is similar to season of pollen exposure, has been reported previously in college students [121].…”
Section: Ar and Depressionmentioning
confidence: 75%
“…It is possible that the latitude and bioclimatic differences between the two countries could explain the contradictory results. Alternative biological factors have been proposed as triggers of suicide in spring, such as the marked tree pollen peaks in spring (Postolache et al 2005) which could result in seasonally increased cytokine production in upper airways resulting in increased exacerbation of mood disturbance in spring (Guzman et al 2007). Consistent with these hypotheses, intranasal tree pollen administration in previously sensitized rodents results in increased cytokine expression in the brain and behavioral alterations consisting of increased anxiety and disturbed social interaction (Tonelli et al 2009) .…”
Section: Discussionmentioning
confidence: 99%
“…17 Several recent studies have suggested associations between mood disorders or suicidality and a seasonal presentation associated with pollen counts. [19][20][21][22] A recent review discusses the evidence for a link between allergy and depression and notes the available reports on possible relationships between allergy, montelukast, and suicidality. 23 Acknowledging these background rates of suicidality in the general population and the apparently higher rates of suicidality in the asthmatic and allergic populations, it could be anticipated that some patients being treated for asthma or allergic rhinitis with montelukast could report suicidal ideation or behavior.…”
Section: Discussionmentioning
confidence: 99%